Design of pineapple outer contour measurement device based on triangulation - LI Ying; DONG Yao; WANG Kaibin; HE Zifen; YUAN Hao (Shipin yu jixie)
ObjectiveTo solve the problem that pineapple dimensions are not easy to obtain and lack of processing data during the processing of pineapple automated peeling machine.MethodsThe cylindrical coordinate system was used to describe the positional coordinates of the pineapple surface points, the required parameters were calculated by combining the contact measuring method and triangulation method, the overall scheme of the pineapple outer contour measuring mechanism was designed, the static force and buckling analysis of the measuring rod was carried out by ANSYS, and the experimental bench was built to carry out the verification experiments.Resultsthe maximum stress of the measuring rod during the measurement process was 32.463 MPa, and the maximum deformation was 0.21 mm, which meets the requirements of structural rigidity; The maximum error of the measurement test was 1.8 mm, which could be controlled within 1%, and the average measurement time was 31.6 and 35.2 s.ConclusionThe measurement accuracy and time of the experimental setup can satisfy the needs of the pineapple's actual production and processing.